The Crystal Structure of the Human Titin:Obscurin Complex Reveals a Conserved yet Specific Muscle M-Band Zipper Module. Issue 4 (27th February 2015) - Pernigo, Stefano; Fukuzawa, Atsushi; Pandini, Alessandro; Holt, Mark; Kleinjung, Jens; Gautel, Mathias; Steiner, Roberto A.
Abstract: M10 is the most C-terminal immunoglobulin (Ig) domain of the giant protein titin and a frequent target of disease-linked mutations. Currently, it is the only known muscle Ig domain able to interact with two alternative ligands—obscurin and obscurin-like-1 (Obsl1)—in different sarcomeric subregions. Obscurin and Obsl1 use their homologous N-terminal Ig domain (O1 in obscurin and OL1 in Obsl1) to bind M10 in a mutually exclusive manner. We present here the X-ray structure of the human titin:obscurin M10:O1 complex extending our previous work on the M10:OL1 interaction. Similar to M10:OL1, the M10:O1 complex displays a chevron-shaped antiparallel Ig–Ig architecture held together by a conserved molecular interface, which we validated by isothermal titration calorimetry and sorting experiments in neonatal rat cardiomyocytes. O1, although structurally related to OL1 and M10, both members of the intermediate set (I-set) Ig family, presents an intriguing switch of its βA′ strand. This leads to structural differences between the complexes, particularly for the "open side" of the chevron-shaped assembly. A bioinformatics analysis reveals that the βA′-switch observed for O1 is rare and that it is involved in mediating protein–protein interactions. Molecular dynamics simulations also suggest that this topological alteration substantially increases local flexibility compared to the conventional I-set Ig domains. The O1/OL1 Ig domains are candidate discriminatory structural modules potentially directing the binding of specific additional partners at the M-band. Cellular sorting experiments in neonatal rat cardiomyocytes are consistent with the view that the titin:obscurin/Obsl1 complexes might be a platform for higher-order interactions. Graphical Abstract: Highlights: The structure of the muscle titin:obscurin (M10:O1) complex has been elucidated. The O1 obscurin domain displays an unconventional I-set Ig-fold. The M10:O1 complex is compared to the titin:obscurin-like-1 (M10:OL1) complex. M10:O1 and M10:OL1 differences might direct other specific partners at the M-band.